Digital Transformation and Organizational Culture of Small and Medium Size Enterprises - Rutihinda, Cranmer (Archives of Business Research, 2019)
Digital transformation process is a relatively new phenomena that is uniquely different form information technological infrastructures changes of the past. There is no proven track record, or established guidelines from which firms can follow or adopt. To undertake digital transformation pioneering firms have to improvise as they attempt to reconfigure their organizational process to take advantage of these emerging technologies. Building on contributions from organizational research this study has explores the role of organizational culture in the digital transformation processes of small and medium size enterprises. It builds on the competing values framework to categorize the organizational culture. Factor analysis identified three archetypes of organizational cultures from the studied sample, that is, the adhocracy culture, the market culture, and the hierarchical culture. As hypothesized, results from the study find small and medium size enterprises with a market oriented organizational culture, as well as, those having an adhocracy organizational culture to have greater intensity of digital transformation. On the other hand, there was no significant relationship between firms with hierarchical organizational culture and digital transformation intensity. Small firms with greater internet business experience